N-Aroylbenzotriazoles as Efficient Reagents for o-Aroylation in Absence of Organic Solvent - Phungpis, Baramee; Hahnvajanawong, Viwat (Asian Journal of Chemistry, 2021)
N-Aroylbenzotriazoles have been shown to be efficient reagents for esterification in the absence of organic solvent. Grinding of N-aroylbenzoytiazoles with twofold excess of alcohols for a couple of hours at room temperature gave corresponding esters in high percentage of yields.